IMPLEMENTASI METODE PEMBELAJARAN IDEAL PROBLEM SOLVING BERDASARKAN GAYA KOGNITIF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS X SMA NEGERI 7 BANJARMASIN PADA MATERI MINYAK BUMI - Muhammad Al Amin; Mahdian Mahdian; Arif Sholahuddin (Universitas Lambung Mangkurat, 2015)
Abstract. The purpose of this research is to determine the difference in critical thinking skills of students who have learnt with Identify the problem, define the problem, Explore solution, Act on the strategy, and Look back and evaluate the effect (IDEAL) Problem Solving method and the students who have learnt with conventional methods based on cognitive styles on material of Petroleum. The method of this research is a quasi-experiment and the design is nonequivalent control group design. The population of this research was class of X SMAN 7 Banjarmasin in year academic 2012/2013. The Samples were determined by purposive random sampling by 2 classes out of 7 classes. The Data collection technique using tests and observation. The Analysis technique using t-test and descriptive analysis. T-test was used to analysing the difference in students' critical thinking skills with cognitive style Field Independent (FI) and Field Dependent (FD) in the experimental class and the control class. The results showed that: there is a significant difference critical thinking skills among students who have learnt with IDEAL Problem Solving method and students who have learnt with conventional method based on cognitive styles on the material of Petroleum and cognitive styles affect students' critical thinking skills.Keywords: ideal problem solving, cognitive styles, field independent (FI), field dependent (FD), critical thinkingskills, petroleum.